Study of blood component therapy in obstetrics - Pancholi, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Blood transfusion is a life saving measure. Various pregnancy complications and disorders of labor present as risk factors for extra blood loss during pregnancy and cause severe hemodynamic instability. This along with complications due to abortion (spontaneous or induced) and ruptured ectopic pregnancy show up as conditions needing transfusion in the day-to-day practice of obstetrics. In a country like India, limited and fixed resources of blood, forces us to titrate the use of blood and its components. Normally, blood loss during birth is well-tolerated because of changes during pregnancy. Methods: This is a retrospective observational study done at tertiary care hospital. This study is based on study of indoor patients admitted during one year duration. Detailed history and all necessary investigations were carried out. Details regarding blood transfusion were taken indication of blood transfusion, number and type of unit transfused, number of patients given blood components, indications where single unit was transfused. Analysis of the data was done. Results: Anemia followed by antepartum hemorrhage followed by postpartum hemorrhage was the major cause for blood and blood product transfusion. Approximately 60% patients required two units of PCV (Packed Cell Volume) transfusion. Anemia in pregnancy was the major cause of single unit PCV transfusion. Conclusions: A proper knowledge for blood and blood product transfusion is needed to make it available for people who are actually in need and also to decrease the economic burden. Measures to prevent anemia should be implemented. Active management of third stage of labour (AMTSL) should be done to avoid postpartum hemorrhage. Single unit transfusion should be avoided.